Heroin friendship: life experiences of drug addicts from the individual perspective in their environment - Danışmaz Sevin, Meryem; Erbay, Ercüment (Journal of Dependence, 2021)
Objective: The aim of this study is to make visible life experiences of substance addicts within the micro and mezzo system, which is the rings of the ecological approach. Method: Descriptive analysis was used in this study designed with qualitative research method. In-depth interviews were conducted with twelve substance addicts who were receiving inpatient treatment for the second time between November 2016 and February 2017 in Alcohol and Substance Addiction Treatment Center (AMATEM). Results: As a result of in-depth interviews, it was revealed that these individuals defined themselves as addicted, used multiple substances, used the substance in ruins, cars and / or burials during the first crisis they experienced. In addition, the participants stated that they met on a common ground in AMATEM about substance use during treatment, formed a social network, and disconnected communication with their friends who did not use substances during the treatment process. Conclusion: A good analysis of the role of social environments of individuals, which are effective at every stage of the addiction process, to improve/ support or prevent/ restrict the treatment process, and it has been concluded that active involvement of the micro and mezzo system in treatment will be one of the most effective methods in combating addiction.